Kajian Konseptual Perilaku Hedonis: Perspektif Experiential, Perspektif Epistemik, dan Perspektif Religi - Pramesti, Muthia; Mayasari, Iin; Putri, Niken Iwani Surya (Universitas Brawijaya, Indonesia, 2015)
This paper aims to examine the conceptual basis of hedonic behavior from consumers'perspective. The purpose of the analysis of the conceptual approach is to describe thebehavior of hedonistic, therefore it can strengthen the understanding of concepts based ontheoretical basis. In addition, a conceptual understanding can provide a strategic analysisin order to look hedonistic behavior of a number of perspectives. These different perspectivesprovide a diversity of analysis and hedonistic behavior argument. This study uses perspectivesin order to analyze hedonic behavior. The results showed that, the test model of hedonicbehavior is a function of perspektif experiential, epistemic, and religion.